Investigation of discharge and groundwater contamination characteristics around the Karasu spring, Mus area, Turkey - Çetindag, B (Springer, 2005)
The study area is 35 km east of the city center of Mu, Turkey. The rock units in the area include Paleozoic Bitlis Metamorphites, Cenozoic flysch and Solhan Volcanities and Pliocene formations. A long-term discharge change was monitored in the Karasu spring. The amount of water discharged by the spring during June 3 and October 11, 2002 was 7.18 x 10(6) m(3) while its storage capacity during May 26 and November 11, 2002 was 4.42 x 10(6) m(3).NH4 - N, NO2 - N, NO3 - N, total PO4 - P, SO4 and total organic carbon (TOC) contamination were determined in the recharge area of the spring and other well and spring waters in the vicinity. NH4 - N, NO2 - N, NO3 - N, total PO4 - P, SO4 and total organic carbon contamination around the Budak, Sivbasi, Golbasi, Sazlikbasi and Altinova villages are well above the drinking water standards of the Turkish Standard Institute (TSE) and World Health Organization (WHO) (1984). Similarly, water samples of K-4, K-5 and K-6 branches of the Karasu spring and S-1, S-2, S-3 and S-4 points in the swamp area yielded concentrations much more than limit values.
Keywords: storage capacity; discharge coefficient; contamination; protection area; Karasu spring; Turkey